2019
DOI: 10.1037/emo0000509
|View full text |Cite
|
Sign up to set email alerts
|

Exerting cognitive control under threat: Interactive effects of physical and emotional stress.

Abstract: Individuals with stressful occupations, such as law enforcement and military personnel, are required to operate in high stakes environments that can be simultaneously physically and emotionally demanding. These individuals are tasked with maintaining peak performance under stressful and often unpredictable conditions, exerting high levels of cognitive control to sustain attention and suppress task-irrelevant actions. Previous research has shown that physical and emotional stressors differentially influence suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
1
10
2
Order By: Relevance
“…In contrast to the results of Cantelon et al (2019), who observed effects of physical stress to be restricted to the low emotional stress condition, our results provide no evidence for a canceling-out effect between emotional and physical stress. Similarly, no evidence was observed for the assumption that a combination of high emotional and physical stress would lead to additionally negative effects on task performance (Nieuwenhuys & Oudejans, 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the results of Cantelon et al (2019), who observed effects of physical stress to be restricted to the low emotional stress condition, our results provide no evidence for a canceling-out effect between emotional and physical stress. Similarly, no evidence was observed for the assumption that a combination of high emotional and physical stress would lead to additionally negative effects on task performance (Nieuwenhuys & Oudejans, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Perceived intensity was measured using a 10-point scale (1 = none/no distress ; 10 = agonizing/unbearable distress ) during the work-up procedure and throughout the experiment to ensure that participants would not exceed a score of 4 ( uncomfortable ). In line with previous studies (Cantelon et al, 2019; Grillon et al, 2004; Robinson et al, 2013), emotional stress was manipulated on a block-by-block basis during the task, with order randomized within participants and exercise conditions (i.e., light vs. vigorous intensity). Participants were informed about threat versus no-threat by means of a visual indicator on the screen (visible throughout the block).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated that invoking a higher stress response can also increase cognitive performance. In a study on perceived threat of electric shock, subjects with increased anxiety demonstrated faster reaction time in executive tasks under the threat of unpredictable shocks to the hand (Cantelon et al, 2018). In studies on physical exertion in athletes, higher stress responses from exertion were associated with faster reaction times (Luft et al, 2009; Murray and Russoniello, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Future work should also consider the psychological factors that are at play in realistic exercise scenarios (e.g., anticipatory anxiety before athletic performance, cognitive stress during military operations) that may influence motivation in lab-based research. For example, acute anxiety experienced during exercise has been shown to mitigate declines in inhibitory control under long duration, high intensity exercise ( Cantelon et al, 2019 ). Additionally, research has demonstrated that mental resource allocation, perception of effort and prefrontal cortex activation are differentially affected when exercise end-point is known vs. unknown ( Radel et al, 2017 ; Wingfield et al, 2019 ), yet it remains unknown how such anticipation may influence cognitive function during exercise.…”
Section: What Is Next?mentioning
confidence: 99%